2009
DOI: 10.1007/s00421-009-1211-6
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic ultrasonography is a valid method to measure changes in skeletal muscle cross-sectional area

Abstract: The purpose of this study was to examine the reliability and validity of the "panoramic" brightness mode ultrasonography (US) method to detect training-induced changes in muscle cross-sectional area (CSA) by comparison with results obtained using magnetic resonance imaging (MRI). Out of 27 young male volunteers, 20 subjects were assigned to training group and seven to non-training control group. Muscle CSAs of vastus lateralis were analyzed by MRI and US before and after 21 weeks of either heavy resistance tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
157
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(173 citation statements)
references
References 21 publications
13
157
1
2
Order By: Relevance
“…US has been previously used and validated in muscle architecture imaging studies, 2,11,12,15 including a comparison between US imaging and MRI to measure the cross-sectional area of the lumbar multifidus and the vastus lateralis muscles. 1,10 The results of the present study show that measurements using US imaging of the lumbar spinous processes in sagittal plane motion are reliable and generally consistent with those taken by MRI. It is important to note that the small number of subjects in the present study resulted in mostly nonsignificant differences, based on t tests comparing the US and MRI measurements.…”
Section: Discussionsupporting
confidence: 82%
“…US has been previously used and validated in muscle architecture imaging studies, 2,11,12,15 including a comparison between US imaging and MRI to measure the cross-sectional area of the lumbar multifidus and the vastus lateralis muscles. 1,10 The results of the present study show that measurements using US imaging of the lumbar spinous processes in sagittal plane motion are reliable and generally consistent with those taken by MRI. It is important to note that the small number of subjects in the present study resulted in mostly nonsignificant differences, based on t tests comparing the US and MRI measurements.…”
Section: Discussionsupporting
confidence: 82%
“…According to Ahtiainen et al, muscle CSA, as measured by ultrasonography, is associated directly with hypertrophy. 16 A strong correlation between CSA and muscle strength or contractile capacity has also been shown. 17 Therefore, this measurement directly reflects hypertrophy, and ultrasound is a valid and reproducible method for this measurement.…”
Section: Discussionmentioning
confidence: 94%
“…They used a compounding technique of ultrasound images, but only a half-round compound scanner, to assess the quadriceps CSA and found that the ultrasound muscle CSA was 30% lower than the CT-measured value at the same site. 3 Over the last 10 years, a limited number of studies [4][5][6][7] have evaluated limb muscle CSA using a technique of compounding ultrasound images. Unfortunately, at this moment, the ultrasound compounding technique to assess muscle CSA is not widely used, which may be due to it being a cumbersome procedure.…”
Section: Introductionmentioning
confidence: 99%